Muhammad Baqir Al-Shadr’s Thoughts in Building A Fair Economic System - Nasrudin Nasrudin; Ani Fatimah Zahra Saifi (Universitas Islam Lamongan, 2023)
This study aims at analyzing and exploring Muhammad Baqir Al-Shadr's thoughts on the fair economic system. This study uses a descriptive qualitative approach, with document review. The results of this study conclude that the economic problem does not lie in the production or scarcity of resources, but rather due to the problem of unequal and unfair distribution as a result of the economic system allowing the exploitation of the strong against the weak. In addition, Baqir Al-Shadr argues that the Islamic economic system must be more comprehensive, in-depth and rooted in Islamic justice values.